Modeling and optimization of a network of energy hubs to improve economic and emission considerations. (15th December 2015) - Maroufmashat, Azadeh; Elkamel, Ali; Fowler, Michael; Sattari, Sourena; Roshandel, Ramin; Hajimiragha, Amir; Walker, Sean; Entchev, Evgueniy
Abstract: Energy hubs that incorporate a variety of energy generation and energy transformation technologies can be used to provide the energy storage needed to enable the efficient operation of a 'smart energy network'. When these hubs are combined as a network and allowed to exchange energy, they create efficiency advantages in both financial and environmental performance. Further, the interconnectedness of the energy network design provides an added layer of reliability. In this paper, a complex network of energy hubs is modeled and optimized under different scenarios to examine both the financial viability and potential reduction of greenhouse gas emissions. Two case studies consisting of two and three energy hubs within a network are considered. The modeling Scenarios vary according to the consideration of distributed energy systems and energy interaction between energy hubs. In the case of a network of two energy hubs, there is no significant economic or emissions benefit with only a 0.5% reduction in total cost and 3% reduction in CO2 emission. In the case of a network of three energy hubs, there is a significant economic benefit ranging from 11% to 29%, and 11% emission reduction benefit, as well as a 13% reduction in natural gas consumption. Highlights: The generic form of the modified energy hub concept with network model is presented. Two case studies are presented to demonstrate the benefits of energy hub network. Distributed energy is shown to provide economic and environmental advantages. Multi criteria optimization of the economic and environmental performance is done.